Transfering Sustainability Competences through Green Pedagogies and Service-Learning in Higher Education - Cantalejo, María J.; Aldaya, Maite M.; Navarlaz, Isabel (European Journal of Sustainable Development, 2025)
Sustainability competences are reflected in the ability to look ahead to change and shape the future of the societies in which they live through active participation in the sense of sustainable development. Through service-learning, students take responsibility for their actions. The complex nature of sustainability issues makes it useful to explore problems and their solutions holistically. In the framework of the NEMOS project (A New Educational Model for Acquiring Sustainability Competences through Service-Learning), a collaborative process was initiated to pool the knowledge and experience of five Higher Education Institutions working together to implement new educational models for effectively acquiring sustainability competences through service-learning in food-related degrees. This EU-funded project was launched and aimed to advance the transition to sustainability education through practical and innovative educational approaches and interventions. Green pedagogy can support transformative learning through the exploration and clarification of learners